Peran Incremental Capital Output Ratio untuk Mengukur Efisiensi Modal Terhadap Pertumbuhan Ekonomi - Irfan, Taufik Muhammad; Daryono, Daryono (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This study discusses the role of Incremental Capital Output Ratio (ICOR) in measuring the efficiency of capital allocation and its impact on economic growth in Indonesia from 2008 to 2023. ICOR is used to evaluate the relationship between additional output and additional capital in an economy. Data analysis shows that ICOR varies from year to year, reflecting fluctuations in capital allocation efficiency. The results show that a decrease in ICOR value corresponds to an increase in efficiency in capital use to achieve significant economic growth. Multiple linear regression analysis also revealed that ICOR has a significant influence on economic growth, where changes in capital allocation efficiency affect overall economic performance. In addition, interest rates also have a significant impact on economic growth, with an increase in interest rates tending to inhibit economic activity and Gross Domestic Product (GDP) growth. The implication of this study is the importance of capital allocation efficiency management and interest rates in designing economic policies to support sustainable economic growth in Indonesia